Tidewater Disaster Mitigation through Training Integrated with Healthy Sugar and Healthy Fish Processed - Rusana, Rusana; Rachmawati, Indra; Parnowo, Suko; Karseno, Karseno; Naufalin, Rifda; Wulan, Tyas Retno (Global Health Science Group, 2024)
Ujunggagak Village is an area prone to flooding often caused by high tides. The community has not utilized the potential of existing natural resources optimally due to a lack of knowledge and skills in processing them. This service aims to increase knowledge and skills in processing coconut sap into healthy sugar and processed healthy sea fish in communities affected by disasters. Service method with education and training on using natural preservatives for penderes farmers and fishermen women groups (KWN). The number of group members is 30 penderes and 25 KWN. The service was carried out for three months. The level of knowledge was measured before and after the education was carried out using a questionnaire. Group skills are measured through quality production results after training. The results show an increase in the knowledge of the Penderes group from 20% poor to 76.7% good, while in the KWN it increased from 28% poor to 80% in the good category. The group skill of the penderes increases from 0% to 100% producing healthy sugar in the form of coins, batteries, and healthy palm sugar. KWN's skills have gone from just making salted fish to being skilled at processing seafood in the form of healthy meatballs, sausages, nuggets, and crackers. This activity can be sustainable and continue to be developed so that it can improve the health and economic status of the community. The community can anticipate crop failure as a result of flood disasters.